Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Stratigraphy, age and correlation of two widespread Late Holocene tephras preserved within Lake Kutubu, Southern Highlands Province, Papua New Guinea - Larissa Schneider; Brent V. Alloway; Russell J. Blong; Geoff S. Hope; Stewart J. Fallon; Colin F. Pain; William A. Maher; Simon G. Haberle (Journal of Quaternary Science, 2017)
Sediment cores were retrieved from Lake Kutubu, the largest upland lake in Papua New Guinea, to assess palaeoenvironmental baselines. Two prominent tephra layers were encountered within the cores. Using a combination of core stratigraphy, sediment properties and geochemical characterization (electron microprobe and laser ablation inductively coupled‐plasma mass spectrometry techniques) we were able to correlate these tephras with Tibito and Olgaboli tephras, both previously described at adjacent distal localities. Glass shard compositional data of Tibito tephra from Lake Kutubu, Kuk swamp and from proximal volcaniclastic successions from Long Island are indistinguishable and this similarity strongly supports Long Island as the eruptive source. For Olgaboli tephra, the location of its eruptive source is less certain but the glass shard compositional data indicate a Karkar Island source. The occurrence of Tibito and Olgaboli tephras in Lake Kubutu sediments extends their known distributions further south‐west into the southern Highlands region and affirms their importance as inter‐regional stratigraphic markers, of late Holocene age, that have considerable potential for use in future palaeoenvironmental, archaeological and volcanic hazard and/or impact studies. Copyright © 2017 John Wiley & Sons, Ltd.

Vegetation and environments since the Last Glacial Maximum in the Southern Tablelands, New South Wales - JUSTINE KEMP; GEOFF HOPE (Journal of Quaternary Science, 2014)
Regional changes in vegetation and environment in the last 16 ka have been reconstructed from Micalong Swamp and Willigobung Swamp (35°S) on the western Southern Tablelands of New South Wales (NSW). Micalong Swamp lies at 980 m above sea level (a.s.l.), which is close to the subalpine treeline at this latitude. Willigobung Swamp (780 m a.s.l.) approaches the modern ecotone between dry and wet montane forest formations. The sites are sensitive to shifts in temperature and precipitation and are the first reported pollen records from the western montane slopes of NSW. A radiocarbon‐based chronology indicates that Micalong Swamp was a swampy, gravel floodplain surrounded by alpine grassland before 16.1 ka. Subalpine woodland may have become established at 1000 m by 16–14 ka. Organic fen sedimentation developed

Pollen‐based reconstructions of biome distributions for Australia, Southeast Asia and the Pacific (SEAPAC region) at 0, 6000 and 18,000 14 C yr BP - Elizabeth J. Pickett; Sandy P. Harrison; Geoff Hope; Kate Harle; John R. Dodson; A. Peter Kershaw; I. Colin Prentice; John Backhouse; Eric A. Colhoun; Donna D'Costa; John Flenley; John Grindrod; et al. (Journal of Biogeography, 2004)
Aim This paper documents reconstructions of the vegetation patterns in Australia, Southeast Asia and the Pacific (SEAPAC region) in the mid‐Holocene and at the last glacial maximum (LGM). Methods Vegetation patterns were reconstructed from pollen data using an objective biomization scheme based on plant functional types. The biomization scheme was first tested using 535 modern pollen samples from 377 sites, and then applied unchanged to fossil pollen samples dating to 6000 ± 500 or 18,000 ± 1000 14 C yr bp . Results 1. Tests using surface pollen sample sites showed that the biomization scheme is capable of reproducing the modern broad‐scale patterns of vegetation distribution. The north–south gradient in temperature, reflected in transitions from cool evergreen needleleaf forest in the extreme south through temperate rain forest or wet sclerophyll forest (WSFW) and into tropical forests, is well reconstructed. The transitions from xerophytic through sclerophyll woodlands and open forests to closed‐canopy forests, which reflect the gradient in plant available moisture from the continental interior towards the coast, are reconstructed with less geographical precision but nevertheless the broad‐scale pattern emerges. 2. Differences between the modern and mid‐Holocene vegetation patterns in mainland Australia are comparatively small and reflect changes in moisture availability rather than temperature. In south‐eastern Australia some sites show a shift towards more moisture‐stressed vegetation in the mid‐Holocene with xerophytic woods/scrub and temperate sclerophyll woodland and shrubland at sites characterized today by WSFW or warm‐temperate rain forest (WTRF). However, sites in the Snowy Mountains, on the Southern Tablelands and east of the Great Dividing Range have more moisture‐demanding vegetation in the mid‐Holocene than today. South‐western Australia was slightly drier than today. The single site in north‐western Australia also shows conditions drier than today in the mid‐Holocene. Changes in the tropics are also comparatively small, but the presence of WTRF and tropical deciduous broadleaf forest and woodland in the mid‐Holocene, in sites occupied today by cool‐temperate rain forest, indicate warmer conditions. 3. Expansion of xerophytic vegetation in the south and tropical deciduous broadleaf forest and woodland in the north indicate drier conditions across mainland Australia at the LGM. None of these changes are informative about the degree of cooling. However the evidence from the tropics, showing lowering of the treeline and forest belts, indicates that conditions were between 1 and 9 °C (depending on elevation) colder. The encroachment of tropical deciduous broadleaf forest and woodland into lowland evergreen broadleaf forest implies greater aridity. Main conclusions This study provides the first continental‐scale reconstruction of mid‐Holocene and LGM vegetation patterns from Australia, Southeast Asia and the Pacific (SEAPAC region) using an objective biomization scheme. These data will provide a benchmark for evaluation of palaeoclimate simulations within the framework of the Palaeoclimate Modelling Intercomparison Project.